2002
DOI: 10.1046/j.1445-5994.2002.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of nausea and vomiting after chemotherapy: what is the evidence?

Abstract: The control of nausea and vomiting is an important problem for patients undergoing chemotherapy. With the introduction of newer agents, including 5-HT3 antagonists, nausea and vomiting control after chemotherapy has much improved but is not always optimal. While there is an intrinsic limitation to the efficacy of anti-emetic drugs, their efficacy can be further reduced if the drugs are not used appropriately. In some circumstances newer anti-emetics may be unnecessary and better nausea and vomiting control may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In the other study, tropisetron was more effective than conventional agents such as metoclopramide and chlorpromazine but drug selection was empirical and deficiencies in the study design, as reported, meant the results were at a high risk of bias [21]. Because the chronic nausea associated with advanced cancer is multifactorial and involves many different receptor systems, the large body of evidence for the treatment of acute nausea and vomiting due to highly emetogenic chemotherapy has not been considered [42]. Because of concerns over toxicity, such as constipation, and the cost of therapy, more well-designed studies of the 5HT3 receptor antagonists for the nausea associated with far-advanced cancer are needed.…”
Section: Discussionmentioning
confidence: 96%
“…In the other study, tropisetron was more effective than conventional agents such as metoclopramide and chlorpromazine but drug selection was empirical and deficiencies in the study design, as reported, meant the results were at a high risk of bias [21]. Because the chronic nausea associated with advanced cancer is multifactorial and involves many different receptor systems, the large body of evidence for the treatment of acute nausea and vomiting due to highly emetogenic chemotherapy has not been considered [42]. Because of concerns over toxicity, such as constipation, and the cost of therapy, more well-designed studies of the 5HT3 receptor antagonists for the nausea associated with far-advanced cancer are needed.…”
Section: Discussionmentioning
confidence: 96%
“…In clinical trials with humans, treatment with 5‐HT 3 antagonists often combined with the corticosteroid dexamethasone during the first chemotherapy treatment reduced the incidence of acute vomiting by approximately 70% (e.g. Bartlett and Koczwara, 2002; Aapro et al ., 2003; Ballatori and Roila, 2003; Hickok et al ., 2003; Andrews and Horn, 2006). However, the 5‐HT 3 antagonists are less effective at suppressing acute nausea than they are at suppressing acute vomiting (Morrow and Dobkin, 1988; Bartlett and Koczwara, 2002; Hickok et al ., 2003) and they are ineffective at reducing instances of delayed (24 h later) nausea and vomiting (Morrow and Dobkin, 1988; Grelot et al ., 1995; Rudd et al ., 1996; Rudd and Naylor, 1996; Tsukada et al ., 2001; Hesketh et al ., 2003) and anticipatory (conditioned) nausea and vomiting (Nesse et al ., 1980; Morrow and Dobkin, 1988; Hickok et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors may include chronic alcohol use, female gender, and a history of poor control of nausea and vomiting (Bartlett and Koczwara 2002 ). Other risk factors may include chronic alcohol use, female gender, and a history of poor control of nausea and vomiting (Bartlett and Koczwara 2002 ).…”
Section: Nausea and Vomitingmentioning
confidence: 99%